2017
DOI: 10.1002/jmri.25757
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T2* relaxation time analysis of articular cartilage of the tibiotalar joint in professional football players and healthy volunteers at 3T MRI

Abstract: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:372-379.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…7). These results are consistent with previous clinical studies which reported increased T2* relaxation time on the regions of increased articular cartilage contact loads [37][38][39]. Although those clinical measurements must be the result of long-term response to altered joint loading, our relatively short three-month study suggests that the changes in the articular cartilage extracellular matrix may be initiated at the early stage of load variations.…”
Section: Discussionsupporting
confidence: 92%
“…7). These results are consistent with previous clinical studies which reported increased T2* relaxation time on the regions of increased articular cartilage contact loads [37][38][39]. Although those clinical measurements must be the result of long-term response to altered joint loading, our relatively short three-month study suggests that the changes in the articular cartilage extracellular matrix may be initiated at the early stage of load variations.…”
Section: Discussionsupporting
confidence: 92%
“…It was further supported by positive correlations between regional variations in articular cartilage contact strain and T2* relaxation time (Fig 7). These results are consistent with previous clinical studies which reported increased T2* relaxation time on the regions of increased articular cartilage contact loads [37][38][39]. Although those clinical measurements must be the result of long-term response to altered joint loading, our relatively short three-month study suggests that the changes in the articular cartilage extracellular matrix may be initiated at the early stage of load variations.…”
Section: Discussionsupporting
confidence: 92%
“…It was further supported by positive correlations between regional variations in articular cartilage contact strain and T2* relaxation time (Fig 7). These results are consistent with previous clinical studies which reported increased T2* relaxation time on the regions of increased articular cartilage contact loads [37][38][39]. Although those clinical measurements must be the result of longterm response to altered joint loading, our relatively short three-month study suggests that the changes in the articular cartilage extracellular matrix may be initiated at the early stage of load variations.…”
Section: Discussionsupporting
confidence: 92%